Desmopressin for treatment of platelet dysfunction and reversal of antiplatelet agents: a systematic review and meta-analysis of randomised controlled trials - Desborough, M; Oakland, K; Crivellari, M; Doree, C; Estcourt, L; Stanworth, S (Wiley, 2017)
Background Platelet dysfunction, including that caused by antiplatelet agents, increases the risk of peri-operative bleeding. The optimal management of patients with platelet dysfunction undergoing surgery is unclear. Objectives To assess whether desmopressin reduces peri-operative allogeneic red cell transfusion and bleeding for patients with platelet dysfunction. Patients/Methods We searched for randomised controlled trials in The Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, Embase, the Transfusion Evidence Library and ISI Web of Science to 7th July 2016. Data were pooled using mean difference (MD), relative risks or Peto odds ratios (pOR) using a random-effects model. Results Ten trials with 596 participants were identified, all in the setting of cardiac surgery. Platelet dysfunction was due to antiplatelet agents in six trials and cardiopulmonary bypass in four trials. Patients treated with desmopressin were transfused with fewer red cells (MD -0.65 units, 95% CI -1.16 to -0.13); lost less blood (MD -253.93 ml, 95% CI -408.01 to -99.85 ml); and had a lower risk of re-operation due to bleeding (pOR 0.39, 95% CI 0.18 to 0.84). Similar results were found for the subgroups with platelet dysfunction due to antiplatelet agents or other causes, with little evidence of statistical heterogeneity between subgroups. The GRADE quality of evidence was very low to moderate suggesting considerable uncertainty over the results Conclusions Desmopressin may be a useful agent to reduce bleeding and transfusion requirements for people with platelet dysfunction or with a history of recent anti-platelet drug administration undergoing surgery.